Green Hospitality Implementation Strategy In Creating Brand Awareness In Ubud Green Resort - Kadek Damayanti; Andhi Supriadi; Hartoyo Soehari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research is to determine and apply green hospitality to brand awareness in Ubud green resort. This type of research is using a qualitative approach. The reason is first, this approach is descriptive, Second, this approach is able to familiarize relationships with research target subjects, Third, this approach is able to provide opportunities to find real conditions in the field. The data collection methods in this study were observation, interviews, and documentation. Data analysis in this study was conducted using interactive models from Huberman, and Saldana (2014), which apply four (4) steps in analyzing data such as data collection, data condensation, data presentation, and data verification. The implementation of green hospitality at Ubud Green Resort includes seven aspects, including: (1) Land use, (2) Energy efficiency, (3) Water conservation, (4) Use of building materials, (5) Indoor air quality, (6) Environmental management, (7) Operational management. Ubud Green Resort has implemented green hospitality successfully but there are several indicators that need to be addressed in the future. By implementing green hospitality, Ubud Green Resort can shape consumer awareness and trust in their brand. This advantage is an effective strategy to create brand awareness that can attract tourists and increase the company's competitiveness amid the rapid movement of the accommodation industry